Considerations redarding dimensional structure of sheep and goats farms at regional level - Diana Creţu; Rodica Chetroiu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The paper presents dimensional structure of sheep and goats farms at national level, as well as a comparative analysis of it, conducted at the level of development regions. As of April 30, 2019, there were 338,371 sheep farms, of which 65% were in the category "below 10 heads", belonging to households. At regional level, dimensional structure indicates that, in all areas of the country, most sheep farms are in the category "below 10 heads", between 47% in the West Region and 72% in the South-East. In fact, in the west part of the country, the shares of larger farms are higher than in other areas. Most farms are located in the south-east part of the country, where most of them are in the category under 10 heads. At the same time, there were 134,069 goats farms, of which 83% were in "under 10 heads" category. At regional level, most goats farms are in this category, between 67% in Bucharest-Ilfov region and 91% in the southwest of the country. Also, the largest share of holdings over 50 heads are in Ilfov (11%). It seems that the proximity of the capital has stimulated the development of larger goat farms, whose products are easier to find in the market in Bucharest.
Keywords: Q12; Q19; 330; dimensional structure; farms; sheep; goats; regions